Simulation-Based Team Training Improves Team Performance among Pediatric Intensive Care Unit Staff - Colman, Nora; Figueroa, Janet; McCracken, Courtney; Hebbar, Kiran (Journal of Pediatric Intensive Care, 2019)
Simulation training fosters collaborative learning and improves communication among interdisciplinary teams. In this prospective observational cohort study, we evaluated the impact of interdisciplinary simulation-based team training (SBTT) on immediate learning of team performance behaviors. In a 3-month period, 30 simulation sessions were conducted and 165 staff members, including physicians, nurses, and respiratory therapists, were trained. Regression analysis showed a statistically significant improvement in team performance (p < 0.0001). Study results demonstrate that SBTT is effective in immediate acquisition of optimal team performance behaviors by multidisciplinary pediatric intensive care unit staff, including physicians with higher level subspecialty training in the simulation environment.
Keywords: simulation; team performance; team training